Energy absorption performance of concentric and multi-cell profiles involving damage evolution criteria - Estrada, Quirino (2018)
Many advantages are attributed to concentric and multi-cell columns, respect to single cell structures, which made them useful for applications in automobile design. The current paper analyzes the effect of cross-section on the crashworthiness performance of concentric and multi-cell profiles. Numerical analyses were performed considering damage evolution criteria using Abaqus/Explicit. Structures with triangular, square, hexagonal and circular base cross-sections were considered. In all cases, the structures were made of aluminum alloy EN AW-7108 T6 and modelled with ductile, shear and Müschenborn-Sonne Forming Limit Diagram (MSFLD) damage initiation criteria. The structures were axially loaded/impacted using a striker of 500 kg with an initial velocity of 10 m/s. Booth concentric and multi-cell structures showed an increase in energy absorption (Ea) as their cross-section tend to form a circular shape. The best performance was obtained by the profiles with circular cross-sectional base. In regard to profiles with triangular shape, an increase in crush force efficiency of 76.4% and energy absorption of 60.32%, was observed. Likewise, a better performance of specific energy absorption (SEA) for multi-cell profiles, relative to concentric structures, was obtained in the range from 33% to 57.92%. Finally, we end our study with a typical application in automotive crashworthiness design.